The Polarized Cosmic Hand: IXPE Observations of PSR B1509-58/MSH 15-52 - Romani Roger W.; Wong Josephine; Di Lalla Niccolo; Omodei Nicola; Xie Fei; Ng C. -Y.; Ferrazzoli Riccardo; Di Marco Alessandro; Bucciantini Niccolo; Pilia Maura; Slane Patrick; Weisskopf Martin C.; et al. (IOP Publishing Ltd, 2025)
We describe IXPE polarization observations of the pulsar wind nebula (PWN) MSH 15−52, the "Cosmic Hand." We find X-ray polarization across the PWN, with B-field vectors generally aligned with filamentary X-ray structures. High-significance polarization is seen in arcs surrounding the pulsar and toward the end of the "jet," with polarization degree PD > 70%, thus approaching the maximum allowed synchrotron value. In contrast, the base of the jet has lower polarization, indicating a complex magnetic field at significant angle to the jet axis. We also detect significant polarization from PSR B1509−58 itself. Although only the central pulse phase bin of the pulse has high individual significance, flanking bins provide lower-significance detections and, in conjunction with the X-ray image and radio polarization, can be used to constrain rotating vector model solutions for the pulsar geometry.